Adverse effects of fluid overload in different paediatric age groups - Althagafi, Tariq H.; Qartali, Aminah A.; Alasmari, Nader H.; Alasmree, Abdulrahman D.; Alahmadi, Ahmed S.; Alharbi, Osama A.; Alnakhli, Mohammad M.; Alraddadi, Saba A.; Alkhalifah, Soliman K.; Alhajooj, Zahra N.; Alrehaili, Ruba D. (International Journal Of Community Medicine And Public Health, 2022)
Fluid resuscitation is a routine procedure in the treatment of critically ill patients especially in paediatric intensive care units. Fluid overload can result from instability in fluid homeostasis caused by the administration of excessive fluids. Fluid overload can have a wide range of adverse impacts on paediatric critical care patients, including increased mortality risk. Fluid overload increases the length of hospital stay and ventilation time also elevates requirement for renal replacement treatment. The purpose of this research is to review the available information about adverse effects of fluid overload in different paediatric age groups. Literature suggests that fluid overload is associated with significant morbidity and mortality among children. Fluid overload percentage greater than 10% is linked to higher mortality rates among children. Respiratory failure can be triggered by pulmonary alveolar and interstitial edema caused by hypervolemia. Children suffering from acute kidney injury or other renal diseases experience more worsened conditions in presence of fluid overload. Fluid overload can impair organ performance, which can impact disease and fatality. Excessive fluid may alter the efficiency of the heart and perhaps impair cardiac function by considerably moving ventricular compliance to the right on the Frank-Starling curve. The negative effects of fluid overload make patients more susceptible to an elevated risk of morbidity and death even if fluid overload itself is not a direct indicator of mortality. Further research can in aid in developing preventive and management strategies for the fluid balance in paediatric settings.